Perancangan E-Tajwid Berbasis Android Di RTQ (Rumah Tahfiz Qur’an) Raudhatul As Salimy Gobah Tilatang Kamang - Fried Arianda; Liza Efriyanti; Supratman Zakir; Khairuddin Khairuddin (Jurnal Media Infotama, 2023)
Abstract—This research is motivated by the lack of support for learning media in conveying recitation learning material. One effective and efficient way to increase interest in learning recitation is by designing an Android-based learning media. So that users, especially children aged 8 to 12, are able to read the Qur'an properly and correctly. Learning media for recitation are now available in several forms, including in the form of books, interactive CDs, and e-learning. Books have limitations that they can only display information in the form of text and images, are easily damaged by water or torn, and are difficult to carry around. The Interactive CD form has drawbacks for accessing it because you have to use computer media, the computer requires electrical power. The aspect of mobility is lacking because computers are not easy to carry everywhere. With the above constraints, we need a tool that will facilitate the process of learning to read the Qur'an. The tool meant here is the design of a mobile-based recitation learning media application In designing this internship information system, researchers used DDD-E. Media development using the DDD-E model consists of (1) Decide or set program goals and materials, (2) Design or design, namely creating program structures, (3) Develop or developing is producing media elements and making media appearance, (4) Evaluate or evaluate, namely checking the entire design and development process. The resulting media were tested for the validity, practicality and effectiveness of the product using a questionnaire to assess the product aimed at media experts, teachers and students. The results of the product test that the author did obtained a validity test from 1 validator obtained a value of 0.86 with a very valid category, a practicality test from 2 practicums obtained a value of 0.95 with a very high category, and the effectiveness test of 31 assessors obtained a value of 0, 88 with very effective category. So that the E-Tajwid application can be used as a support in learning the science of recitation